AN INTEGRATED SEVEN QUALITY TOOLS AND 5W+1H QUALITY CONTROL MODEL FOR IMPROVING BOTTLED DRINKING WATER PRODUCTION EFFECTIVENESS - Turang, Frangky; Najoan, Harvard Kaunang; Liow, Festus Evly; Sokuma, Darman (LPPM Universitas Jambi, 2026)
Product quality is a critical factor in improving competitiveness and operational performance in the bottled drinking water industry. This study aimed to develop a quality control model for 285 mL bottled drinking water production using the Seven Quality Tools approach to improve production effectiveness. This research employed a quantitative descriptive case study design. Quality data collected during the production period of January–July 2025 were analyzed using the Seven Quality Tools, including Check Sheet, Stratification, Pareto Diagram, Histogram, Scatter Diagram, Control Chart, and Fishbone Diagram. Improvement strategies were then formulated using the 5W+1H approach. The production volume reached 1,950,000 bottles, with 12,338 defective products, corresponding to a defect rate of 0.63%. The dominant defects consisted of dented bottles (43.35%), insufficient filling volume (31.22%), and folded bottle caps (25.43%). Pareto analysis identified dented bottles as the primary defect requiring immediate corrective action. Fishbone analysis indicated that the major root causes were associated with machine conditions, material handling, operational methods, and human factors. The findings demonstrate that integrating the Seven Quality Tools with the 5W+1H approach provides an effective framework for identifying defect priorities, analyzing root causes, and formulating corrective actions. The proposed quality control model emphasizes preventive maintenance, standard operating procedure standardization, continuous process monitoring, and operator competency development. This model supports continuous quality improvement by reducing defects, improving process stability, and enhancing production effectiveness, while offering a practical reference for quality management implementation in the bottled drinking water manufacturing industry.